Association of ABCG2 rs2231142 Allele and BMI With Hyperuricemia in an East Asian Population - Chen, Yen-Ju; Chen, I-Chieh; Lin, Hsueh-Ju; Lin, Ying-Cheng; Chang, Jui-Chun; Chen, Yi-Ming; Hsiao, Tzu-Hung; Chen, Pei-Chun; Lin, Ching-Heng (Frontiers in Genetics, 2021)
Objectives: Genetic variants and obesity are risk factors for hyperuricemia. Recent genome-wide association studies have identified ABCG2 rs2231142 as one of the most prominent genetic variants for HUA in an East Asian population. Nevertheless, no large-scale studies have demonstrated any interactive effects between this variant and obesity on serum urate level in Asians. This study aimed to determine the interaction of ABCG2 rs2231142 variant and body mass index and its effect on risk of HUA in an East Asian population. Methods: The study was conducted using the Taiwan Biobank database, a population-based biomedical research database of patients with Taiwanese Han Chinese ancestry aged 30 to 70 years between September 2014 and May 2017. Detailed physical information on participants were collected by questionnaires and genotyping using Affymetrix TWB 650K SNP chip. The primary outcome was HUA, defined as a serum uric acid level > 7.0 mg/dL. Odds ratio of HUA was analyzed using logistic regression models and the effects of interaction between ABCG2 rs2231142 variants and BMI on serum uric acid level were explored. Results: We identified 25,245 subjects, 4,228 (16.75%) of whom had HUA. The prevalence of HUA was 30% in men and 3.8% in women. The risk of HUA was significantly associated with ABCG2 rs2231142 risk T allele, with more HUA in TT genotype (OR: 2.40) and TG genotype (OR: 1.64) in men, and TT genotype (OR: 2.42, ) and TG genotype (OR: 1.82 in women, compared with their counterparts. Moreover, we found a strong genetic-environmental interaction associated with the risk of HUA. There was increased risk of HUA by the interaction of ABCG2 rs2231142 variant and BMI for TT genotype (OR: 7.42) and TG genotype (OR: 4.25) in men compared with the GG genotype in men, and for TT genotype (OR: 25.43) and TG genotype (OR: 3.05) in women compared with the GG genotype in women. Conclusions: The risk of HUA was markedly increased by the interaction of ABCG2 rs2231142 variant and BMI, both in men and in women. Body weight control and reduction in BMI are recommended in high-risk patients with the ABCG2 rs2231142 risk T allele.